Research project: strategies to improve reading comprehension skills in children from 6 to 7 years old at a private bilingual school in Guayaquil during the school academic year 2013-2014 - Córdova Reyes, Karen Evelyn (2013)
A serious problem that students from 6 to 7 years old face when studying at bilingual schools is the lack of tools to understand and acquire comprehension strategies while reading different texts. Parents find these skills really difficult for their children to get because comprehension questions or comprehension activities were not a matter of learning in the past, so they feel concerned about this subject at school and transmit that feeling to their children. Teachers have tried to find solutions to overcome these difficulties in the classroom since this subject is not well accepted by kids without the appropriate reading habit…..